Penerapan Balanced Scorecard pada Bisnis Coffe Shop dan Resto di Bogor - Aprizal, Muhamad Dicky; Noviani, Witria; Halawa, Erimina; Suripto (Ikatan Da'i Indonesia, 2024)
This research is in the form of presenting a complete description of a study. The measurements used for the financial perspective are Return On Investment, Sales Growth, and Profits Margin; customer perspective with Customer Satisfaction; internal business perspective with Manufacturing Effectiveness Cycle and Number of Imperfect Products; as well as a growth and learning perspective with Employee Satisfaction, Employee Productivity and Employee Turnover Rate. The research results show that the financial and internal business perspective of the Coffe Shop & Resto Bogor requires improvement. Meanwhile, the customer perspective as well as the growth and learning perspective need to be maintained. So it can be concluded that the Balanced Scorecard can be applied to the management of Coffe Shop & Resto Bogor